2019
DOI: 10.4103/ijem.ijem_149_18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on bone turnover markers in children and adolescents from North India

Abstract: Objectives: Vitamin D is known to play an important role in bone mineral metabolism. Its deficiency may affect growth and status of bone markers in children. Hence, we undertook to study the status of bone markers in children with vitamin D deficiency (VDD) and impact of vitamin D3 supplementation on them. Materials and Methods: Total 468 out of 615 children and adolescents with VDD, who were given either of the three doses (600, 1000, and 2000) of vitamin D supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Hence, the increase in PINP levels is due to the increase in PTH levels. Unlike other studies, which showed either negative (8) or no (29) correlation of CTX with vitamin D, we observed a positive correlation between sCTX and vitamin D with a marked effect observed in premenopausal women. This is in line with a study carried out in Tehran on healthy adolescents (30).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Hence, the increase in PINP levels is due to the increase in PTH levels. Unlike other studies, which showed either negative (8) or no (29) correlation of CTX with vitamin D, we observed a positive correlation between sCTX and vitamin D with a marked effect observed in premenopausal women. This is in line with a study carried out in Tehran on healthy adolescents (30).…”
Section: Discussioncontrasting
confidence: 99%
“…A significant negative correlation was observed between vitamin D and PINP. An increase in PTH levels leads to an increase in PINP levels, indicating that bone remodeling requires an adequate amount of PTH (8,28). Hence, the increase in PINP levels is due to the increase in PTH levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study focused on bone metabolism indicators in patients of different age and gender using HIS data from one hospital, providing mathematical modeling to assist the future study of age and gender in disease research. Although multiple studies have been published that provide a reference for differences in children and adolescents [2][3][4][5][6][7][8], those studies did not provide a precise breakdown of age and gender, namely at what patient age does parameters require precise matching and which age does they not. Researchers believe that age matching should be performed on all subjects in disease control research, but strict age-matching substantially increases the cost and di culty of conducting the study.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical test was made by Mann-Whitney test.DiscussionThe present study focused on bone metabolism indicators in patients of different age and gender using HIS data from one hospital, providing mathmatical modeling to assist the future study of age and gender in disease research. Although multiple studies have been published that provide a reference for differences in children and adolescents[2][3][4][5][6][7][8], those studies did not provide a precise breakdown of age and gender, namely at what patient age does parameters require precise matching and which age does they not. Researchers believe that age matching should be performed on all subjects in disease control research, but strict age-matching substantially increases the cost and The biological data for young individuals is very complicated, and so we established mathematical models to correlate data for people under the age of 20.…”
mentioning
confidence: 99%